Implementasi Metode Topsis Dalam Sistem Pendukung Keputusan Keringanan UKT (Studi Kasus : STIT Madina Sragen) - Nor Wahid Hidayad Ulloh; Ulla Delfana Rosiani; Eka Larasati Amalia (SMATIKA JURNAL : STIKI Informatika Jurnal, 2021)
Economic distinctions that make it difficult to make UKT payments from each student and college student. There are several students parents who because of economic reasons, are reluctant to make UKT payments. At this point, the introduction of decision-making processes in support of institutional leadership decisions is not new. The criteria for getting UKT waivers are also not arbitrary, but there are special criteria given to the recipients of UKT waivers. Supporting criteria include: Parent's Occupation, GPA Value, Length of Study, Study Status and Family Health. According to the analysis, the results obtained using the topsis method in performing the calculation achieve an 87% accuracy result.